Passage efficiency and migration behavior for adult Atlantic salmon at a Half-Ice Harbor fish ladder - Karlsson, Robert (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Due to exploitation of the world’s rivers, the upstream migration of anadromous species is frequently delayed or even prevented. To mitigate these problems and allow fish to migrate past obstacles, structures such as fish ladders have been developed. However, recent studies show that many of the present fish passage facilities are deficient. Monitoring and evaluation of passage facilities is therefore crucial to enable necessary adjustments. In this study I have examined the passage efficiency and the migration behavior for upstream migrating Atlantic salmon (Salmo salar L.) passing a recently built fish ladder in the river Umeälven. 104 salmon were caught, tagged and released in the spillway close to the fish way entrance during the 2012 spawning run. Tagged fish were monitored with several radio telemetry loggers and PIT-antennas (Passive Integrated Transponder). The result revealed a passage efficiency of 78% and a mean delay of 30 days, post-tagging, before passage. Salmon tagged earlier in the season delayed longer before passing the fish way. The majority of salmon visited the entrance pool several times (mean 11.3 visits) before ascending and the time spent in the entrance pool were in general high (mean 2.4 days). The activity in and out from the entrance pool followed a diel rhythmicity but was independent of discharge in the bypass channel. The ladder was visited in average 1.5 times before the final ascent, which took on average 17.7 hours. A delay was observed in the upper part of the ladder in front of the VAKI-system, used to count passing fish. Once past the VAKI-system, there seems to be no problem for the fish to reach river Vindelälven. I also report that the migration pattern passed the fish way did not differ between native salmons from the Ume/Vindelälven stock and strayers with a genetic origin from the Luleälven stock.